An unusual presentation of pulmonary embolism. (9th August 2012) - Lee, Deacon Zhao Jun; Whittaker, Marzena; Al-Mohammad, Abdallah
Abstract : Pulmonary embolism (PE) is a common cardiovascular emergency, by which occlusion of a part of the pulmonary arterial bed may lead to acute life threatening but potentially reversible right ventricular failure. Early diagnosis is fundamental to implement immediate effective treatment to reduce mortality. However, the diagnosis can be easily missed due to non-specific clinical presentation. We wish to present an unusual case whereby a patient with no risk factors for PE, symptoms suggestive of acute pericarditis and an ECG showing concave ST segment elevation was found to have multiple pulmonary emboli.